Potential therapies against SARS-CoV-2 virus evaluated in large-scale clinical trials - Alin-Viorel Focsa; Magdalena Birsan; Maria Dragan; Diana Popovici; Catalina Daniela Stan (Amaltea Medical Publishing House, 2022)
COVID-19 is a viral disease caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The pathogenesis of SARS-CoV-2 infection in humans manifests as mild symptoms to severe respiratory failure. The development of vaccines against coronaviruses faces several inherent challenges in its establishment as safe and effective, but also in production and distribution. Therefore, supportive treatments are more achievable in a short period of time in controlling the pandemic. Treatment is mainly based on controlling symptoms and inhibiting viral replication. Antivirals are more effective the earlier they are administered during the course of the disease, preferably starting from the first days of evolution; the benefit/risk ratio is the higher the patient has a higher risk of severe evolution. That is why antivirals are primarily administered to patients with nonsevere forms of the disease who have risk factors for severe evolution. Immunomodulatory drugs enhance the immune response against pathogens and may offer a therapeutic approach to treatment of viral diseases, having a significant prophylactic activity in the acute respiratory viral infection. There is a strong scientific rationale which suggest that viral diseases respond to immunomodulatory drugs. People protected with antivirals, immunomodulatory drugs or vaccines often have the disease in a milder or asymptomatic form. In Romania, the latest treatment protocol for COVID-19 includes immunomodulatory, antiviral and anti-inflammatory medication.